Parapsoriasis in pediatric age. - Menni, S.; Piccinno, R. (European Journal of Pediatric Dermatology, 2018)
Parapsoriasis is a clinical picture which, although rarely, can be observed in pediatric age. In this article, 7 cases of parapsoriasis affecting subjects under 16 years of age are reported and the diagnostic, prognostic and nosologic difficulties are underlined. The form of parapsoriasis characterized by a single patch and the form characterized by the contemporary presence of both small and large patches were prevalently observed in our group of patients.